Maternal insecurity and failure to thrive in Asian children. Issue 3 (March 1989) - Fenton, T R; Bhat, R; Davies, A; West, R
Abstract : Four Asian babies were investigated because they failed to thrive. In all four cases the failure to thrive was a result of the mother's social isolation and inability to communicate, and to the father's refusal to accept that there was a problem in the family.